Polyphenol Content and Antioxidant Activity of Stevia and Peppermint as a Result of Organic and Conventional Fertilization - Lina Garcia-Mier; Adriana E. Meneses-Reyes; Sandra N. Jimenez-Garcia; Adan Mercado Luna; Juan Fernando García Trejo; Luis M. Contreras-Medina; Ana A. Feregrino-Perez (Journal of Food Quality)
Stevia rebaudiana Bertoni and Mentha piperita are plants that generate interest mainly due to the presence of bioactive compounds in their leaves, such as phenolics. Studies indicate that phenolics have pharmacological and therapeutic properties, including antioxidant activity. Phenolic compounds may be affected by the type of fertilization. For this reason, organic and chemical fertilization were evaluated along with antioxidant activity. Results showed significant differences for total phenols in organic peppermint (62% higher content). Also, DPPH test displayed differences for peppermint and stevia (572% and 16% greater in organic). Organic fertilization may be alternative for producing high added agricultural and commercial products.